Human prostate cancer metastases target the hematopoietic stem cell niche to establish footholds in mouse bone marrow - Shiozawa, Yusuke (American Society for Clinical Investigation, 2011)
HSC homing, quiescence, and self-renewal depend on the bone marrow HSC niche. A large proportion of solid tumor metastases are bone metastases, known to usurp HSC homing pathways to establish footholds in the bone marrow. However, it is not clear whether tumors target the HSC niche during metastasis. Here we have shown in a mouse model of metastasis that human prostate cancer (PCa) cells directly compete with HSCs for occupancy of the mouse HSC niche. Importantly, increasing the niche size promoted metastasis, whereas decreasing the niche size compromised dissemination. Furthermore, disseminated PCa cells could be mobilized out of the niche and back into the circulation using HSC mobilization protocols. Finally, once in the niche, tumor cells reduced HSC numbers by driving their terminal differentiation. These data provide what we believe to be the first evidence that the HSC niche serves as a direct target for PCa during dissemination and plays a central role in bone metastases. Our work may lead to better understanding of the molecular events involved in bone metastases and new therapeutic avenues for an incurable disease.